Analysis results of in situ water and sediment quality of Újpest backwater - Grósz, János; Sebők, András; Nagy, Noémi; Kovács, Andrea; Waltner, István (TÁJÖKOLÓGIAI LAPOK, 2019)
Water is one of the most significant and vulnerable natural resources. The aim of our study presented here was to assess the sediment and water quality of Újpest backwater and its main influencing factors. The study area is located in the north side of Budapest, a backwater of the Danube river. An industrial region of the city, also serving as recreational area for nearby residents. The average water depth is 4,5 meters and the length of the backwater is 2200 meters. The most significant economic activity is the ship-building and maintenance. In order to assess water and sediment quality, a number of physical, chemical and the microbiological measurements were carried out on both water and sediment samples. The water samples were collected at two dates, while sediments samples were taken at one date in 2015. Sediment analysis included heavy metals (Cu, Zn, Pb, Cd), TPH and PAH measurements. Water quality analysis included chemical (NH3, NH4+, NO3-, Fe, pH value, conductivity, dissolved oxygen) and microbiological parameters. The results of the study showed that the sediment contained different types of heavy metals and hydrocarbons due to the industrial activities and transportation. During the analyses, we measured high Pb, Cd, Cu, Zn, TPH and PAH concentration in the northern part of the backwater. Possible reasons of the high values include ship maintenance and repairing, ship traffic and road traffic. Measured high Pb, Cd, TPH and PAH concentrations in the sediment might carry environmental risks. Among the general water quality parameters, we found high Fe concentrations mist likely connected to railway traffic in the northern part of the sampling area, while microbial analysis showed only acceptable or lower counts.